Virus awareness and computer virus problem among the administration employees in district and land offices of Temerloh / Izharudin Lauzan and Mohd Syahrizan Mat Nor - Lauzan, Izharudin; Mat Nor, Mohd Syahrizan (2009)
The purpose of this study was to measure the level of employee's knowledge and awareness on computer virus issues in District and Land office of Temerloh administration department. This study also uses to identify the current problem faced by the employees. Other that, this study need to identify how the computer virus scattered within the offices. The questionnaires was using as a method in conducting this study. The questionnaires has been distributed randomly to the respondent who working in administration department in District and Land office of Temerloh. About 48 respondents have answer the questionnaires distribute. In order to make some improvement to the employees in District and land offices of Temerloh, some suggestion and recommendation was stated.